ChemInform Abstract: Catalytic Enantioselective Conjugate Alkynylation of α, β‐Unsaturated 1, 1, 1‐Trifluoromethyl Ketones with Terminal Alkynes. Issue 43 (7th October 2016) - Sanz‐Marco, Amparo; Blay, Gonzalo; Munoz, M. Carmen; Pedro, Jose R.
Abstract: The first catalytic enantioselective conjugate alkynylation of α, β‐unsaturated 1, 1, 1‐trifluoromethyl ketones is presented to furnish various alkynes bearing a propargylic stereogenic center with excellent enantioselectivities.